Aesthetic Experience of Metabolic Processes - Förster, Desiree (Future Ecologies, 2021)
Simultaneously speculative and inspired by everyday experiences, this volume develops an aesthetics of metabolism that offers a new perspective on the human-environment relation, one that is processual, relational, and not dependent on conscious thought. In art installations, design prototypes, and researchcreation projects that utilize air, light, or temperature to impact subjective experience the author finds aesthetic milieus that shift our awareness to the role of different sense modalities in aesthetic experience. Metabolic and atmospheric processes allow for an aesthetics besides and beyond the usually dominant visual sense.